예비 지구과학 교사들은 교육실습을 통해 무엇을 느꼈을까? -대학 교육과정과 교육실습의 연관성을 중심으로 - 임성만; Lim, Sung-Man (대한지구과학교육학회지, 2017)
The purpose of this study was to find out how pre-service teachers who have gone through training have thought about teaching practice. Specifically, I analyzed the relationship between college curriculum and teaching practice, and what they had felt in teaching practice. The study included 20 third grade students in teacher's college. The results of this study were as follows: First, it was found that the content knowledge and the pedagogical knowledge of the subjects taught at the university were helpful for the teaching practice. Second, they were thought that teaching practice would be helpful just to watch the class. And pre-service teachers felt that class demonstration was a necessary part of becoming a teacher. Third, pre-service teachers said that it is necessary to have a lecture in the university that can have opportunity for class demonstration for teaching practice. And also they wanted to open a lecture to learn various teaching techniques and the newest teaching methods. Fourth, pre-service teachers said that it is important to form relationships with students in order to complete the lessons through the teaching practice. And they said that they felt that the education scene was more powerful and harder than they thought. In addition, they said that through this exercise, it became a moment to feel the importance of thorough preparation and experience. In this way, teaching practice is an essential process for pre-service teachers to become teachers and it can be seen that they have many influences. Based on these results, it is necessary to review and revise the curriculum of the training colleges in relation to the teaching practice. 이 연구는 예비교사들이 교육실습을 통해 무엇을 느꼈으며 교육실습에 대해 어떻게 생각하고 있는지 알아보는 데 목적이 있었다. 특히 이번 연구에서는 예비교사들이 실습기간 동안 느낀 교육실습과 대학 교육과정의 관계를 분석하였다. 연구를 위해 교사 양성 기관에 재학 중인 3학년 학생 20명이 참여하였다. 연구 결과, 첫째, 교육실습을 위해 대학에서 배운 내용학 지식과 교육학 지식과 관련된 교과들이 도움이 되었다고 예비교사들은 응답하였다. 둘째, 예비교사들은 교육실습은 수업을 보는 것만으로도 도움을 줄 수 있다고 응답하였다. 셋째, 예비교사들은 교육실습을 위해 수업시연의 기회가 대학 교육과정 내에서 이루어져야 한다고 생각하였다. 그리고 다양한 교수 기술과 새로운 교수방법을 배울 수 있는 강의가 개설되기를 원하고 있었다. 넷째, 예비교사들은 수업의 완성도를 높이기 위해서는 교사와 학생간의 관계가 중요하다는 것을 이야기하였다. 그리고 이것은 교육현장에서는 그들이 생각한 것보다 더 중요하다는 것을 느꼈다고 응답하였다. 더불어 그들은 이런 교육실습을 통해 많은 것을 경험하는 것은 매우 도움이 된다고 생각하고 있었다. 이러한 결과를 통해 교육실습은 미래 교사가 될 예비교사들을 위해 매우 필수적인 과정이며 많은 영향을 준다는 것을 알 수 있었다. 아울러 교육실습과 관련된 교사 양성 기관의 교육과정에 대한 검토 및 수정이 요구된다고 하겠다.